How effective are health messages/warnings in improving knowledge and awareness of alcohol-related harm? The Slovenian case on using a mobile app - Sandra Radoš Krnel; Igor Pravst; Maša Hribar; Bojan Blažica; Anita Kušar (BMC, 2023)
Abstract Background Consumers generally lack access to information on alcoholic beverages, in spite of it being readily available for food and non-alcoholic beverages. Given the rights of consumers, and as with other products harmful to the population, there have been increasing calls for health warnings to be placed on alcoholic beverages, similar to those implemented on tobacco products. The aim of our research was to assess whether knowledge and awareness of the risks and harms associated with alcohol can be improved with a mobile app. Methods Intervention was conducted using VKJ mobile app, which enables users to scan the barcode of an alcoholic beverage and receive feedback on its labelled alcohol content and estimated energy value. At each search, eleven different health messages/warnings about the risks and harms of alcohol are also displayed randomly, rotating on the screen. A survey was conducted before and after the intervention, to assess the knowledge and awareness of the risks and harms associated with drinking alcohol. Results Significant differences were found for eight of the twelve tested statements. The improvement was seen to a greater extent in the group of high-risk drinkers. The results also showed that the vast majority of participants (78%) who were exposed to the health messages supported mandatory labelling of alcoholic beverages with information on ingredient listing and energy value, and 72% would like to have health warnings on alcohol products. Conclusions The use of a mobile app can be an option to improve knowledge and raise awareness of the risks and harms related to alcohol.